IMPLEMENTASI PENETAPAN PESERTA SERTIFIKASI GURU SMP SWASTA DI KOTA SEMARANG (STUDI DI SMP TEUKU UMAR DAN SMP MUHAMMADIYAH 3) - Lelyana Dwi Jayani; Ida Hayu Dwimawanti; Slamet Santoso (Journal of Public Policy and Management Review, 2013)
Teacher sertification is one way to improve the quality of education and teachers welfare, and serve to enchance the dignity and role of teachers as agents of learning. One important part of teacher sertification is the process of fixing. This study aims to determine how the implementation of the estabilishment of a private junior high school teacher certification participants in Semarang and determine the factors that support or hinder implementation. This study uses a descriptive qualitative method. Data collection is done by literature study, observation and in-depth interviews with a number of informants. Data analysis in qualitative research, according to Miles and Huberman with data reduction, data presentation, and verification.Phenomenon is approached by a model study of public policy implementation by George Edward III in wich the factors that support and hinder the implementation are; communication, resources, disposition, and bureaucratic structure. It can be concluded that the determination of private junior high school teacher certification in Semarang, there are still factors that hinder implementation. It’s because the resources to handle the policy and objectives of the policy (teachers) do not comply with the operational procedures the estabilishment of teacher certification.